Update on adjuvants in regional anaesthesia - Christiansson, Lennart (Array, 2009)
This is a review article on adjuvants to neuroaxial anaesthesia and peripheral nerve blocks used in clinical practice: opioids, asoconstrictors, clonidine, NMDA antagonists, midazolam, glucocorticoids, nonsteroidal anti-inflammatory drugs and neostigmine. Mechanisam and site of action of each of them is described. It is followed by discussion of experimental and clinical data published in the last five years.